2017
DOI: 10.1007/s10508-017-1077-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality Within Female Same-Gender Couples: Definitions of Sex, Sexual Frequency Norms, and Factors Associated with Sexual Satisfaction

Abstract: Despite a growing number of female same-gender (FSG) relationships, couples-based research and interventions have focused primarily on mixed-gender couples. Consequently, research has applied a heteronormative lens to understanding some relationship factors, including sexuality. The current study sought to provide descriptive data regarding frequency and conceptualizations of sex across partners in FSG relationships, as well as to analyze how relationship factors are associated with sexual satisfaction in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 44 publications
3
11
0
3
Order By: Relevance
“…However, women obtained better sexual satisfaction scores than men. This reinforces the fact that a woman's sexual satisfaction, regardless of sexual orientation, is related not only with her physical sexual response, but also with other factors that may have more to do with intimacy, affection, and emotional closeness [3,17,74,76,77]. The fact that same-sex attracted individuals report, in general, high sexual and relationship satisfaction has already been reported by Calvillo et al [32].…”
Section: Discussionsupporting
confidence: 80%
“…However, women obtained better sexual satisfaction scores than men. This reinforces the fact that a woman's sexual satisfaction, regardless of sexual orientation, is related not only with her physical sexual response, but also with other factors that may have more to do with intimacy, affection, and emotional closeness [3,17,74,76,77]. The fact that same-sex attracted individuals report, in general, high sexual and relationship satisfaction has already been reported by Calvillo et al [32].…”
Section: Discussionsupporting
confidence: 80%
“…A review of literature suggested several factors related to sexual satisfaction which women of differing sexual orientation might value differently, such as a lack of internalized homophobia, sexual assertiveness, interpersonal intimacy, monogamy, use of visual sexual materials, novel sex techniques, orgasm frequency, frequency of genital touching, and frequency of sexual activity (Bailey et al, 1994;Hulpert & Apt, 1993;Kurdek, 1991;Scott et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An ecological model of sexual satisfaction among lesbian/bisexual and heterosexual women revealed a similar set of correlates for both groups (social support, relationship satisfaction, sexual function, and depression), whereas internalized homophobia was a significant and inversely related factor for lesbian/bisexual women only (Henderson, Lehavot, & Simoni, 2009). Across studies, stronger associations with sexual satisfaction were found for frequency of genital touching, frequency of orgasm, sexual frequency, strength of desire for sex, emotional intimacy, and sexual intimacy (feelings of closeness and comfort during and after sex) with women in same-gender relationships than women in mixed-gender couples (Birnie-Porter & Lydon, 2013;Cohen & Byers, 2014;Scott, Ritchie, Knopp, Rhoades, & Markman, 2018;Tracy & Junginger, 2007). Blair and Pukall (2014) found that, compared to women in heterosexual relationships, women in same-gender relationships gain more sexual satisfaction from the quality or intensity of sex rather than the frequency of sex.…”
Section: Female Sexual Satisfaction and Sexual Identitymentioning
confidence: 99%
“…This unfriendly term suggested that LBD is a lesbian-specific phenomenon referred to the quantity of sexual activity, devaluing the importance of quality in sexual experience [17••]. LBD is based on the idea of the existence of a standard frequency of sexual activity in couples [18], and sexual distress is not contemplated in most of these studies.…”
Section: Levels Of Sexual Desirementioning
confidence: 99%